Communication—Corrosion Behavior of Tungsten Metal Gate in the Presence of Hydrogen Peroxide at Acidic Medium. (1st January 2017) - Seo, Jihoon; You, Keungtae; Moon, Jinok; Kim, Joo Hyun; Paik, Ungyu
Abstract : Herein, the corrosion behaviors of W metal gates in the presence of H2 O2 at the acidic medium were investigated as a function of dipping time, temperature, and H2 O2 concentration. We determined the kinetic constants (i.e. k w and k h ) based on the experimental data. The activation energy ( E a ) are calculated from the Arrhenius equation. Thermodynamic parameters (Δ G ‡, Δ H ‡, and Δ S ‡ ) for the dissolution were determined based on the Eyring plot. These results investigated in this study will provide researchers the prior information on parameters to control the corrosion behaviors of W metal gates during the chemical mechanical planarization (CMP) process.